FAKTA SEJARAH DALAM CERPEN INDAHNYA PERSATUAN KARYA ODHY’S - Khairul Fuad (tuahtalino, 2019)
This research aims to know the historical facts behind the Odhy’s’s sort story Indahnya Persatuan. As the work of literature relates certainly to the space and time so those contexts will surround it certainly. Historical context denotes the problem which fills in that short story through reading first. Knowing included answering the historical context is used method of qualitative with theory of contextuality and socio-history for revealing the historical facts were appeared. Then, the result of research was found the historical fact related with the horizontal conflict between Dayaknese and Madurese. The other hand, the other historical facts were found as chronological history of that horizontal conflict. The conclusion of result of research was the short story Indahnya Persatuan containing the elements of historical facts were happened in West Borneo. Through those result can be mentioned that the process of literature work related deeply to contextuality, either the space or the time.